Compensated discrete choice and the Slutsky equation - John K. Dagsvik (Statistics Norway, Research Department, 2022)
Consumers often face choice settings in which alternatives are discrete. Examples include choices between variants of differentiated products, modes of urban transportation, residential locations, etc. In this paper compensated price elasticities and a corresponding(aggregate) Slutsky equation for discrete choice models are derived. A remarkable feature of compensated price elasticities in the discrete case is that they usually are not symmetric, as compensated elasticities with respect to a price increase versus a price decrease may be different. Finally, compensated marginal price effects and elasticities are derived for selected examples.
Keywords: C25; C43; D11; 330; Compensated choice; Discrete/continuous choice; Slutsky equation; Marginalcompensated effects